Dimethyl sulfoxide pivaloyl chloride: a new reagent for oxidation of alcohols to carbonyls - Dubey, Abhishek; Kandula, Subba Rao V.; Kumar, Pradeep (Synthetic Communications, 2008)
An efficient procedure for conversion of alcohols to the corresponding carbonyl compounds, an alternative to the classical Swern oxidation, is described. Pivaloyl chloride is employed as a mild and inexpensive electrophile. A possible reaction mechanism is proposed.
Keywords: Alcohols; carbonyls; DMSO; pivaloyl chloride; Swern oxidation

Desymmetrization approach to the enantiopure syn/anti-1,5-diols via hydrolytic kinetic resolution (hkr) of functionalized meso-bis-epoxides: further elaboration to syn/syn-1,3,5-triols and application to the formal synthesis of cryptocarya diacetate - Kumar, Pradeep; Chowdhury, Partha Sarathi; Pandey, Menaka (Advanced Synthesis & Catalysis, 2013)
A new approach has been developed for the synthesis of enantiopure syn/anti-1,5-diols by desymmetrization of functionalized meso-bis-epoxides using hydrolytic kinetic resolution (HKR). The usage of this protocol was demonstrated by converting syn-1,5-diols into syn/syn-1,3,5-triols and its subseqent application to the formal synthesis of cryptocarya diacetate.
Keywords: bis-epoxides; cryptocarya diacetate; desymmetrization; stereoselective reduction; synthetic methods

Dinuclear salen cobalt complex incorporating Y(OTf)(3): enhanced enantioselectivity in the hydrolytic kinetic resolution of epoxides - Patel, Deepak; Kurrey, Ganesh Ram; Shinde, Sandip S.; Kumar, Pradeep; Kim, Geon-Joong; Thakur, Santosh Singh (RSC Advances, 2015)
The activation of inactive Jacobsen's chiral salen Co(II) (salen = N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine) compound is attained by dinuclear chiral salen Co(III)-OTf complex formation with yttrium triflate. The yttrium metal not only displays a promoting effect on electron transfer, but also assists in forming two stereocentres of a Lewis acid complex with Co(III)-OTf. We found that the binuclear Co-complex significantly enhanced reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its analogous monomer and kinetic data are also consistent with these results.